THE INFLUENCE OF SESSIONS OF LENGTHEN IN THE SENIOR AGE - Rodrigues, Bernardo Minelli (2013)
The aim of this study was to assess the trainability of flexibility in the elderly undergoing stretching sessions. The study included 10 subjects (n = 10), aged between 62 and 68 year old male, who had not participated in programs with stretching exercises. Were done 12 weeks of intervention by stretching exercises performed twice a week, lasting between 30 and 45 minutes each session. The IPAQ (classified as sedentary) and medical release was used as criteria for inclusion. Was performed pre and post test by evaluating coxofemural goniometry. Was made to verify the homogeneity of the sample through the Shapiro Wilk, t test for paired samples, p